Determining Evidence-Based Outcomes in School-Aged Youth: Free-Access Instruments for School Counselor Use. Issue 1 (January 2018) - Bardhoshi, Gerta; Cobb, Nicole; Erford, Bradley T.
School counselors must demonstrate effectiveness of counseling services in a cost-effective manner. This article reviews and applies commonly used, free-access assessment instruments for use with school-aged youth to provide evidence of effective individual, small-group, and large-group interventions. We present instruments assessing depression, anxiety, disruptive behavior, and trauma, so that school counselors can learn basic administration, scoring, interpretation procedures, and psychometric utility to allow immediate use with diverse students.